THE HIGH YIELD OF COTTON IS THE MAIN FACTOR IN SEED PRODUCTION - Qodirov Otabek Abdullahayevich; Usmonov Mirzohid Sobirjon o’g’li; Qurbonov Axmadillo Abduvali o'gli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. In our country, as in all spheres, radical reforms are being carried out in agriculture. In particular, the Decree of the President of the Republic of Uzbekistan dated 02.16.2019 "Seed growing adopted a new version of the law. The main goal of the law is to regulate relations in the seed industry. These documents define the mandate and structure of organizations working in the seed field.